Standardization and High-Performance Thin Layer Chromatographic Fingerprint Profiling of Manjishtha (Rubia Cordifolia L.) Roots (AYUSHDHARA, 2025)
In Ayurvedic medicine, Manjishtha (Rubia cordifolia L.), a perennial climbing herb, is well recognized for its Raktashodhana (blood-cleansing) activity and its therapeutic use in Kuṣṭha (skin disorders), Vraṇa (wounds), and Prameha (urinary ailments). Its roots contain anthraquinones responsible for diverse pharmacological effects. Objective: To evaluate the pharmacognostic, physicochemical, and phytochemical properties of Manjishtha roots and develop a High-Performance Thin Layer Chromatographic (HPTLC) fingerprint for authentication and standardization. Methods: Collected roots were authenticated and were analysed as per Ayurvedic Pharmacopoeia standards through macroscopic, transverse and powder microscopic examinations. An analysis of physicochemical parameters such as moisture loss, ash values, solvent extractives, and pH was carried out. Alcoholic and aqueous extracts were screened for phytochemicals. High-Performance Thin Layer Chromatographic profiling was performed on silica gel GF 60 254 plates using Toluene: Ethyl Acetate: Formic Acid (7:3:1), scanned densitometrically at 254 and 366nm. Results: Roots were cylindrical, reddish-brown, and brittle, with microscopic features showing cork, cambium, phloem, xylem, and pith. Powder microscopy showed the presence of xylem elements, phloem fibres, lignified vessels and fibres. Physicochemical analysis indicated 0.39% foreign matter, 10% total ash, 24.53% alcohol-soluble extractives, 10.70% water-soluble extractives, and pH 6. Phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, tannins, glycosides, carbohydrates, phenol and steroids. The HPTLC chromatogram revealed 12 bands (Rf 0.006–0.958) at 254nm and 11 bands (Rf 0.006–0.976) at 366nm. Conclusion: The study establishes comprehensive pharmacognostic, physicochemical, and HPTLC data for Manjishtha (Rubia cordifolia L.) root, providing a valuable standard for identification and future research applications.